Understanding and representation of organizational training programs and their evaluation - M. Ruiz; J.I. Igartua; M. Mindeguia; M. Orobengoa (International Journal of Production Management and Engineering)
The evaluation of the organizational training is a necessary strategy to guarantee the quality of the training activities in organizations. This research had as an initial objective the development of the first phase of a project funded by the EIT Raw Materials in the “Call for KAVA Education projects”. It officially started on January 2019. The main aim of this research was to define a training program for workers of a specific industrial sector and to evaluate the impact of the skill acquisition of workers through the training program. This paper presents the initial part of the project, the authors were part of the team at that stage. This phase was helpful to obtain the resulting conceptual model from the analysis of the variables involved in an effective learning process. The research tool used for variable identification were three Group Model Building (GMB) sessions with the partners of the project. The resulting model of this paper was helpful to represent through Systems Thinking the phases of a learning process and its evaluation.